Plants diversity of farm forestry in Tanah Laut District, South Kalimantan - MOCHAMAD ARIEF SOENDJOTO; SUYANTO SUYANTO; HAFIZIANNOOR HAFIZIANNOOR; AAN PURNAMA; AHMAD RAFIQI; SYUKRAINY SJUKRAN (Society for Indonesian Biodiversity, 2008)
Both monoculture and polyculture farm forestry were in Tanah Laut District. The plants forming the monoculture farm forestry were rubber, teak, coconut, and acacias. The areas of rubber farm forestry were scattered all over the district. Based on Surat Kepala Dinas Kehutanan Kabupaten Tanah Laut No. 522/202/PPHH/Dishut, there were 43 plant species in the polyculture one; 16 species were categorized as the farm wood and 27 as the other wood. Based on Surat Keputusan Menteri Kehutanan No. SK 272/Menhut-V/2004, there were 44 plant species and 16 of those were the multi purpose tree species. The density and the potential of plants indicated the preference of the community to plant the non-wood producing species of the farm-wood group as well as durian and rambutan of the other wood one.Â© 2008 Jurusan Biologi FMIPA UNS SurakartaKey words: plant diversity, farm forestry, Tanah Laut District.